Development of a Self-Determination Theory-Based Physical Activity Intervention for Aged Care Workers: Protocol for the Activity for Well-being Program - Lock, Merilyn; Post, Dannielle; Dollman, James; Parfitt, Gaynor (Frontiers in Public Health, 2018)
Despite the well-established benefits of regular participation in physical activity, many Australians still fail to maintain sufficient levels. More self-determined types of motivation and more positive affect during activity have been found to be associated with the maintenance of physical activity behaviour over time. Need-supportive approaches to physical activity behaviour change have previously been shown to improve quality of motivation and psychological wellbeing. This paper outlines the development of a need-supportive, person-centred physical activity program for frontline aged-care workers. The program emphasises the use of self-determined methods of regulating activity intensity (affect, rating of perceived exertion and self-pacing) and is aimed at increasing physical activity behaviour and psychological wellbeing. The development process was undertaken in six steps using guidance from the Intervention Mapping framework: i) an in-depth needs assessment (including qualitative interviews where information was gathered from members of the target population); ii) formation of change objectives; iii) selecting theory-informed and evidence-based intervention methods and planning their practical application; iv) producing program components and materials; v) planning program adoption and implementation, and vi) planning for evaluation. The program is based in Self-Determination Theory and provides tools and elements to support autonomy (the use of a collaboratively developed activity plan and participant choice in activity types), competence (action/coping planning, goal-setting and pedometers), and relatedness (the use of a motivational interviewing-inspired appointment and ongoing support in activity).